2021
DOI: 10.1111/cpr.13039
|View full text |Cite
|
Sign up to set email alerts
|

Oral intake of Lactobacillus plantarum L‐14 extract alleviates TLR2‐ and AMPK‐mediated obesity‐associated disorders in high‐fat‐diet‐induced obese C57BL/6J mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…The postbiotics like exopolysaccharide from Lactobacillus plantarum L-14 could inhibit the differentiation of immature cells into mature adipocytes, as well as control body weight gain and lipid profiles in mice by upregulating the TLR2-AMPK signaling pathway [ 85 ]. Besides, the long-chain polyphosphate from Lactobacillus brevis could improve intestinal inflammation and intestinal barrier function by activating the extracellular regulated protein kinases (ERK) signaling pathway [ 91 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…The postbiotics like exopolysaccharide from Lactobacillus plantarum L-14 could inhibit the differentiation of immature cells into mature adipocytes, as well as control body weight gain and lipid profiles in mice by upregulating the TLR2-AMPK signaling pathway [ 85 ]. Besides, the long-chain polyphosphate from Lactobacillus brevis could improve intestinal inflammation and intestinal barrier function by activating the extracellular regulated protein kinases (ERK) signaling pathway [ 91 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…However, no extensive literature is present. Currently, there are few studies related to postbiotics in the periodontal setting [49][50][51][52]; conversely, their use in implantology has not been investigated to date. The outcomes of this study illustrate that postbiotics are as effective as chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
“…TLR2, which plays an important role in the formation the NLRP3/ASC/pro-caspase-1 complex (18,59), is indicated as a potential key mediator between gut bacteria and inflammation (60). It was found that the oral administration of Lactobacillus plantarum can lead to the inhibition of TLR2 in a murine high-fat-diet (HFD) model of obesity (61). Besides, studies performed on TLR2-deficient mice demonstrated that TLR2 could sense gut microbial ligands that can induce remote signaling in the liver endothelium (62).…”
Section: Discussionmentioning
confidence: 99%